The natural history of occult or angiodysplastic gastrointestinal bleeding in von Willebrand disease. (7th November 2014) - Makris, M.; Federici, A. B.; Mannucci, P. M.; Bolton‐Maggs, P. H. B.; Yee, T. T.; Abshire, T.; Berntorp, E.
Summary Recurrent gastrointestinal bleeding is one of the most challenging complications encountered in the management of patients with von Willebrand disease (VWD). The commonest cause is angiodysplasia, but often no cause is identified due to the difficulty in making the diagnosis. The optimal treatment to prevent recurrences remains unknown. We performed a retrospective study of VWD patients with occult or angiodysplastic bleeding within the setting of the von Willebrand Disease Prophylaxis Network (VWD PN) to describe diagnostic and treatment strategies. Centres participating in the VWD PN recruited subjects under their care with a history of congenital VWD and gastrointestinal (GI) bleeding due to angiodysplasia, or cases in which the cause was not identified despite investigation. Patients with acquired von Willebrand syndrome or those for whom the GI bleeding was due to another cause were excluded. Forty‐eight patients from 18 centres in 10 countries were recruited. Seven individuals had a family history of GI bleeding and all VWD types except 2N were represented. Angiodysplasia was confirmed in 38%, with video capsule endoscopy and GI tract endoscopies being the most common methods of making the diagnosis. Recurrent GI bleeding in VWD is associated with significant morbidity and required hospital admission on up to 30 occasions. Patients were treated with multiple pharmacological agents with prophylactic von Willebrand factor concentrate being the most efficient in preventing recurrence of the GI bleeding. The diagnosis and treatment of recurrent GI bleeding in congenital VWD remains challenging and is associated with significant morbidity. Prophylactic treatment with von Willebrand factor concentrate was the most effective method of preventing recurrent bleeding but its efficacy remains to be confirmed in a prospective study.